2015
DOI: 10.5296/jmr.v7i2.6991
|View full text |Cite
|
Sign up to set email alerts
|

Audit Committee and Audit Fees in Malaysia: The Moderating Role of Political Connection

Abstract: The Malaysian corporate governance regime underwent significant enhancement through the revamp of the Bursa Malaysia Listing Requirements (BMLR) in 2008 in respect of audit committee characteristics in order to address adverse market perceptions of its relationship based economy with the strong presence of politically connected (PCON) firms. This study investigates whether such reforms have made a difference. We examine if PCON firms have higher audit fees post implementation of BMLR 2008 on audit committee ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…Prior studies on the effectiveness of the audit committee expertise based on audit fee have been conducted in the developed economies like the United States of America (such as [23,26], the United Kingdom [11,25]; Australia (such as [22,24]; and France [4] among others. The few studies conducted in the developing countries were largely done in Malaysia [16,[27][28][29]. Most of these studies had reported a positive and significant relationship between audit committee expertise and audit fee.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior studies on the effectiveness of the audit committee expertise based on audit fee have been conducted in the developed economies like the United States of America (such as [23,26], the United Kingdom [11,25]; Australia (such as [22,24]; and France [4] among others. The few studies conducted in the developing countries were largely done in Malaysia [16,[27][28][29]. Most of these studies had reported a positive and significant relationship between audit committee expertise and audit fee.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…An audit committee team with financial expertise has the tendency of reviewing the contents in the financial statement; evaluating those areas requiring the work of the committee on technical and decision making as some areas in the financial statement are subjective in nature; and, lowering the risk of internal control failure through reviewing of effective internal control and internal audit effectiveness which can motivate the external auditor to set a lower audit risk thereby reducing lower audit fee charged by the auditor [29,30]. In contrast, [23,16,4,28,26,11,25] revealed that audit committees with financial expertise would require high audit quality from the external auditor by demanding more thorough audit efforts as well as request the auditor to devote sufficient time and efforts to the audit exercise, thereby increasing the audit fee charged by the auditor on its client. More so, an audit committee with financial expertise may demand for a more thorough and higher quality audit to protect itself from any accounting scandal and meet regularly with the auditor to discuss audit matters and discuss the way forward to reduce audit failure, thereby leading to higher audit costs [31,32].…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing monitoring by audit committees also associated with increase in audit fees (Ismail et al, 2012). According to Norziaton et al (2015), PCON firms have higher audit fees due to improved governance which demands an increase in audit effort. Further, the association between audit committee independence, diligence, and expertise and audit fee is significant, suggesting that PCON firms are committed to strong corporate governance and are prepared to pay a higher quality external audit work.…”
Section: Resultsmentioning
confidence: 99%